Nova centralidade em Mossoró (RN): expansão urbana e o bairro Bela Vista - Melo, Emanuelle Roberta da Silva (2014)
This research aims to reconstruct the process of the recent expansion of the urban area of Mossoró (RN), particularly the dynamics of the Bela Vista neighborhood has been established as a new urban centrality. We start from the perspective that the process of urbanization as a result of the transformation of the capitalist system have profound impacts on the restructuring of urban space, which includes resetting and training of new urban centralities. The basic assumption accepts that recent economic changes have led to the adoption of new strategies for the location of large commercial equipment and services, contributing to urban expansion and redefinition of its centrality, leading to the formation of new urban centralities. The research strategy adopted consists of a case study oriented based on the analysis of qualitative information, but also incorporates quantitative information. Interviews with qualified informants were conducted, as well as field surveys, photographic documentation, in order to grasp the phenomenon observed. The survey results show that the Bela Vista neighborhood can be considered a new urban center, housing the specialized trade and service activities, as well as townhouses, which differentiates it from other areas of the city